(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the condition of legal regulation of institute of delegation of legislative powers in the Republic of Kazakhstan is considered, comparison with other states is carried out. In article the reasons of emergence and essence of the relevant institute reveal, its need locates, practice of application of institute of delegation of legislative powers in the Republic of Kazakhstan and foreign countries is considered.Besides, on the basis of the comparative analysis of this institute specific proposals on improvement of the legislation in this sphere become. Key words: Constitution, the President, law, delegations of legislative powers, referendum, legislature, executive power, ratification, statement.